Striving for Synergy: Gender analysis and indigenous social work practice in South Africa - Hochfeld, T (Social Work/Maatskaplike Werk, 2002)
This article argues that excellent social work practice is not possible in the current South African context without taking into account the issue of gender. Firstly, the meaning of "gender analysis" is ex-plored. The historical roots of the gender disparity in South Africa is traced and the current status of women is outlined. Gender analysis is shown to be a useful tool to understand the developmental issues that are being faced today, and compelling reasons for incorporating gender into social work practice are explored in the context of contemporary South Africa. Resonance between gender analysis and indigenous social work practice are explored and clarified, and the relevance of gender analysis for indigenous practice is affirmed. The article concludes with a discussion of some of the possible reasons for the seeming absence of gender analysis in contemporary indigenous practice.